Preoperative Prevention of Surgical-Site Infection in Spine Surgery. (September 2021) - Franker, Lauren M.; Pretet, Molly; Douglas, Barbara; Simmons, Kristin; Wilson, Amber; Roche, Ariel; Milano, Rose
Abstract : Surgical-site infections (SSI) contribute to increased hospital length of stay, readmission rates, cost, and morbidity and mortality rates. The spine service line at a suburban Level II trauma center encountered 2 SSIs among the spine fusion population within a 6-month period. This did not meet the organization's internal benchmark of zero. A pilot quasi-experimental design was used to determine whether preoperative cleansing with 2% chlorhexidine gluconate (CHG)–impregnated cloths versus current practice of bathing with 4% CHG solution would reduce SSIs. Infection rates were measured using simple percentages. Level of significance was p < .05. Outcome data showed a reduction in SSIs from 3.9% to 1.9% with use of 2% CHG-impregnated cloths. There was no significant difference found between the use of 2% CHG-impregnated cloths and 4% CHG solution ( p = .524). This quality improvement change, combined with a strengthened preoperative bundle approach, has permanently been adopted within the spine service line. From October 2017 to March 2021, the spine service line has had zero SSIs within the spine fusion population.